Chapter 1 Introduction Comprehending and Investigating Populist Communication From a Comparative Perspective - Reinemann, Carsten (Routledge Studies in Media, Communication, and Politics, 2019)
First, the authors in this collection begin with the assumption that populism can only be fully understood if the role played by communication and the media is taken seriously. Second, the authors in this volume argue that our understanding of populism can hugely benefit from systematic comparisons of various national contexts, various groups of actors or organizations, and different types of media.